Unrecognized diversity and distribution of soil algae from Maritime Antarctica (Fildes Peninsula, King George Island) - Rybalka, Nataliya; Blanke, Matthias; Tzvetkova, Ana; Noll, Angela; Roos, Christian; Boy, Jens; Boy, Diana; Nimptsch, Daniel; Godoy, Roberto; Friedl, Thomas (Frontiers in Microbiology, 2023)
Eukaryotic algae in the top few centimeters of fellfield soils of ice-free Maritime Antarctica have many important effects on their habitat, such as being significant drivers of organic matter input into the soils and reducing the impact of wind erosion by soil aggregate formation. However, the phylogenetic and species diversity of soil algae in this region is poorly known. Therefore, the study's goal was a precise assessment of the soil algae species diversity of Meseta, a mountain crest of Fildes Peninsula, which is hardly influenced by the marine realm and anthropogenic disturbances. With a focus on the four algal classes of eukaryotic algae, Chlorophyceae, Trebouxiophyceae, Ulvophyceae, and Xanthophyceae, we anticipated capturing key groups of cold-adapted algae communities in the surface barren soils, except for the diatoms and cyanobacteria. Paired-end (ITS2) sequencing metabarcoding, complemented by a clone library approach, revealed a surprisingly high diversity of 830 algal OTUs, assigned to 58 genera in the four targeted algal classes. Members of the green algal class Trebouxiophyceae predominated in the soil algae communities. The major part of the algal biodiversity, 82.5 % of all algal OTUs, could not be identified to the species level due to insufficient representation in reference sequence databases. The classes Ulvophyceae and Xanthophyceae exhibited the most unknown species diversity. In the small portion of algal OTUs for which their distribution could be assessed, full ITS2 sequence identity with references shows the soil algae likely have a wide distribution beyond the Polar regions. They likely originated from soil algae propagule banks in far southern regions, transported by aeolian transport over long distances. About 9 % of the species diversity was shared with that of an exemplary temperate site in Germany. The soil algae communities were highly similar in their composition between the northern and southern parts of the Meseta. The dynamics and severity of environmental conditions at the soil surface, determined by high wind currents, and the soil algae’s high adaptability to harsh environmental conditions may account for this.